Indonesian Community Risk Perception of COVID-19 in 2022 - Mila Tejamaya; Amelia Anggarawati Putri; Sapto Budi Nugroho; Ira Safhira (The Indonesian Journal of Occupational Safety and Health, 2023)
Introduction: In line with the increasing number of COVID-19 cases from July to early August 2022, this paper aimed to analyze the perception of COVID-19 among Indonesians. Methods: A cross-sectional online study on COVID-19 risk perception was conducted in the first week of July 2022. A questionnaire adapted from ECOM (Effective Communication in Outbreak Management for Europe) was distributed online through social media to obtain information about the respondents' knowledge, behavior, and risk perceptions on COVID-19. Results: There were 775 respondents. Most of them were female (61.3%), lived in the eight most targeted areas (84.1%), were unmarried (52.5%), held a bachelor's degree (38.5%), and were Muslims (80.8%). The percentages of respondents who had been infected with COVID-19 were (43.8%). Most participants believed that their knowledge level of the disease was average and above average (>91%). Of the respondents, 83.6% perceived the seriousness of COVID-19 as serious and very serious. However, the anxiety level among these respondents was moderate (slightly and quite anxious). This indicates that even though most respondents still see COVID-19 as a serious disease, their level of fear is decreasing. Compared to a previous study, most respondents in the current study were more confident of their ability to control the risks associated with the transmission of the virus. Nevertheless, they still believe that outdoor activity and not using a face mask can significantly increase the probability of getting infected. Conclusion: The risk perception of COVID-19 in Indonesian community among our study population was appropriate.